Synthetic Plant Cuticle Coating as a Biomimetic Moisture Barrier Membrane for Structurally Colored Cellulose Films. Issue 7 (20th January 2023) - Anusuyadevi, Prasaanth Ravi; Singha, Shuvra; Banerjee, Debashree; Jonsson, Magnus P; Hedenqvist, Mikael S.; Svagan, Anna J.
Abstract: Photonic films based on cellulose nanocrystals (CNCs) are sustainable candidates for sensors, structurally colored radiative cooling, and iridescent coatings. Such CNC‐based films possess a helicoidal nanoarchitecture, which gives selective reflection with the polarization of the incident light. However, due to the hygroscopic nature of CNCs, the structural colored material changes and may be irreversibly damaged at high relative humidity. Thus, moisture protection is essential in such settings. In this work, hygroscopic CNC‐based films are protected with a bioinspired synthetic plant cuticle; a strategy already adopted by real plants. The protective cuticle layers altered the reflected colors to some extent, but more importantly, they significantly reduced the water vapor permeance by more than two orders of magnitude, from 2.1 × 10 7 (pristine CNC/GLU film) to 12.3 × 10 4 g µm m −2 day −1 atm −1 (protected CNC/GLU film). This expands significantly the time window of operation for CNC/GLU films at high relative humidity. Abstract : A biomimetic water barrier strategy, based on a synthetic cuticle coating, is developed to protect structurally colored cellulose films from moisture. The protective cuticle coating reduced the water vapor permeance by more than two orders of magnitude. This significantly expands the time window of operations at high relative humidity.